A REPRESENTATION FOR THE SUPPORT FUNCTION OF A CONVEX BODY - Aramyan, R.H.; Manucharyan, A.G. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2015)
In this paper a formula for a translation invariant measure of planes intersecting a n-dimensional convex body in terms of curvatures of 2-dimensional projections of the body was found. The paper also gives a new simple proof of the representation for the support function of an origin symmetric 3-dimensional convex body, which was obtained by means of a stochastic approximation of the convex body.